Academic Leadership and Career Success: Investigating the Mediating Role of Teamwork Quality in Private Higher Education in Province of Bali - Paramarta, Wayan Arya; Supartha, I Wayan Gede; Dewi, I Gusti Ayu Manuati; Surya, Ida Bagus Ketut (Journal of Ecohumanism, 2025)
This study investigates the influence of academic leadership on the career success of lecturers at private higher education institutions in Province of Bali, with a focus on the mediating role of teamwork quality. Employing a quantitative approach using SEM-PLS, data were collected from 330 lecturers through stratified random sampling. The results demonstrate that academic leadership positively and significantly impacts both career success and teamwork quality. Furthermore, teamwork quality itself has a positive and significant effect on career success. Notably, teamwork quality serves as a mediating factor, strengthening the relationship between academic leadership and career success. These findings underscore the importance of academic leadership and teamwork quality in fostering career success within the context of private higher education.